Muscle Performance in Patients with Fibromyalgia Syndrome - Halim Yılmaz,; Hatice Uğurlu,; Ali Sallı, (Archives of Rheumatology, 2007)
Objective: To compare muscle performance of women with Fibromyalgia syndrome (FMS) to that of healthy women. Patients and Methods: A hundred women applying with common body pain and diagnosed with FMS, and fifty healthy women were included into the study. In all participants, dominant hand grip strength with a hand manometer, maximal knee flexion, extension and shoulder abduction and adduction muscle strength at 60 and 180º/sec angle velocity, 180º/sec angle velocity, dynamic muscle endurance with 30 time repeated maximal isokinetic knee flexion and extension knee flexion and extension with isokinetic device, and static muscle endurance with maintaining the stable position were measured. Relative values were provided by dividing muscle performance parameters which are isokinetically defined to the body weight of the patients. In the patients' group, general pain experienced and regional pain felt after a static endurance tests were determined using Visual Analogue Scale (VAS). Results: When compared with healthy controls, all parameters of muscle performance were significiantly lower in the patients with FMS (33% at hand grip strength, 26-40% at isokinetic measurements and 55-71% at static muscle endurance). Relative isokinetic muscle performance parameters were also significantly decreased (22-36%). Conclusion: In this study, insufficiency in muscle performance was found in patients with FMS. İnsufficiency was more defined in activities requiring prolonged static contraction. These findings suggest the importance of exercises which require prolonged static contractions in the treatment of FMS. (Rheumatism 2007; 22: 43-7)